Herbal Phytomedicine ‘Irisolidone’ in Chronic Diseases: Biological Efficacy and Pharmacological Activity - Patel, Dinesh K. (Recent Advances in Anti-Infective Drug Discovery, 2022)
Background: Plant-derived products have been used in medicine as a source of bioactive molecules, mainly due to their medicinal importance and therapeutic potential. Nowadays, plant derived products have been used in the medicine for the development of novel drug leads. Polyphenols are an important class of secondary metabolites found to be present in plants and their derived products. Polyphenols play an important role in the nutrition of human beings and also have a significant role in plant resistance against pests and diseases. Scientific studies have proven the biological importance of flavonoids in medicine and other allied health sectors. Anti-oxidant, analgesic, anti-microbial, anti-inflammatory, anti-viral, anti-tumor and anti-allergic activities are the important pharmacological features of flavonoids. Irisolidone is an important isoflavone found to be present in Pueraria lobata flowers. Methods: To know the medicinal importance and therapeutic potential of irisolidone in the medicine, numerous scientific research data have been collected from Google, Google Scholar, PubMed, Science Direct, and Scopus. Pharmacological activity data of irisolidone has been collected and analyzed in the present works to know their health beneficial aspects in the medicine. Detailed pharmacological activities of irisolidone have been investigated through scientific data analysis of scientific research works. Results: Scientific research data analysis of irisolidone revealed the anti-inflammatory, antiangiogenic, anti-cancer, anti-platelet, anti-oxidant, anti-hyperlipidemic, immunomodulating, hepatoprotective and estrogenic potential. However, the biological effect of irisolidone on the gastric system, aldose reductase enzymes, malignant gliomas, and JC virus has also been investigated. Scientific data analysis revealed the significance of analytical tools for the separation and identification of irisolidone. Conclusion: Present work signified the biological importance and therapeutic potential of irisolidone in medicine.
Keywords: immunomodulating